Morphological and productive response of corn with sulfur supply in different sources (Research, Society and Development, 2023)
S deficiency is mostly due to the low natural fertility of tropical soils. Especially in Cerrado soils where this deficiency is even more recurrent, which makes it a limiting factor for agricultural production. The objective of this work was to evaluate the increase in productivity and the efficiency of S uptake in maize depending on the application at different doses and sources. Four treatments arranged in randomized blocks were tested, with four replications: control, elemental S0 (S - 19.5% and Ca - 6%) (leaf route - 2.0 L ha-1), agricultural gypsum (S - 15 % and Ca - 18% - 1.8 t ha-1) + elemental S0 and agricultural gypsum. The agronomic and productive characteristics were evaluated. The results were submitted to analysis of variance, F test, and Tukey's mean test was applied. Significant differences were observed as a function of variations in S supply at different phenological stages, it is observed that S provided better morphological development in maize. In the evaluated parameters, the presence of S0 via foliar, associated or not with agricultural gypsum, presented better performance. It can be stated that there is an increase of 53%, and increases of 19% and 15% for the isolated use of S0 and gypsum, respectively. Thus, it was observed that the different forms of S supply in fertilization provide significant differences in the morphological and productive parameters of corn.